AstroSat and NuSTAR observations of XTE J1739−285 during the 2019–2020 outburst. Issue 4 (24th March 2023) - Beri, Aru; Sharma, Rahul; Roy, Pinaki; Gaur, Vishal; Altamirano, Diego; Andersson, Nils; Gittins, Fabian; Celora, T
ABSTRACT: We report results from a study of XTE J1739−285, a transient neutron star low mass X-ray binary observed with AstroSat and NuSTAR during its 2019–2020 outburst. We detected accretion-powered X-ray pulsations at 386 Hz during very short intervals (0.5–1 s) of X-ray flares. These flares were observed during the 2019 observation of XTE J1739−285. During this observation, we also observed a correlation between intensity and hardness ratios, suggesting an increase in hardness with the increase in intensity. Moreover, a thermonuclear X-ray burst detected in our AstroSat observation during the 2020 outburst revealed the presence of coherent burst oscillations at 383 Hz during its decay phase. The frequency drift of 3 Hz during X-ray burst can be explained with r modes. Thus, making XTE J1739−285 belong to a subset of NS-LMXBs which exhibit both nuclear- and accretion-powered pulsations. The power density spectrum created using the AstroSat -laxpc observations in 2020 showed the presence of a quasi-periodic oscillation at ∼0.83 Hz. Our X-ray spectroscopy revealed significant changes in the spectra during the 2019 and 2020 outburst. We found a broad iron line emission feature in the X-ray spectrum during the 2020 observation, while this feature was relatively narrow and has a lower equivalent width in 2019, when the source was accreting at higher rates than 2020. Hard X-ray tail was observed during the 2019 observations, indicating the presence of non-thermal component in the X-ray spectra.